PENYULUHAN HIPERTENSI MELALUI PELATIHAN SENAM HIPERETENSI PADA LANSIA DI KELURAHAN LEMPUING RATU AGUNG KOTA BENGKULU - Astuti, Maryani; Hermasnyah, Hermansyah; Septiyanti, Septiyanti; Annuri, Kheli fitria; Nugroho, Nehru (Poltekkes Kemenkes Bengkulu, 2024)
Hypertension is a circulatory system disorder that causes blood pressure to rise above normal values. Hypertension or high blood pressure is a disorder in the blood vessels that results in the blood supply and oxygen carried by the blood being blocked to the body tissues that need it. Efforts to implement Hypertension Gymnastics for blood pressure control are carried out by increasing the knowledge of the Elderly The importance of checking and controlling blood pressure with hypertension exercises in Bengkulu City. The target of this counseling activity is the residents, especially the elderly in Lempuing District. The implementation method uses the lecture method with material presentation techniques on hypertension and hypertension gymnastics training followed by demonstrations and discussions, Focus Group Discussions (FGD), Observation, while the problem of the ability to develop the knowledge of the elderly is solved by providing training. This activity is packaged in the form of a workshop. There is an improvement